2023
DOI: 10.3390/su15129526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Geometry on Growth, Water Productivity, and Fruit Quality of Tomatoes under Different Soil Moisture Regimes

Abstract: The present study investigated the impact of planting spacing on tomato crop growth, water productivity, and fruit quality under different water regimes. Thus, a field experiment was conducted using a randomized complete block design in a factorial arrangement of treatments. The tomato plants were grown at three planting spacing patterns: 30 cm row-to-row planting spacing, 60 cm row-to-row planting spacing, and 90 cm row-to-row planting spacing, which were marked as (G1), (G2), and (G3), respectively. For each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Therefore, the LAI is an important indicator for measuring the growth characteristics of plant populations. An earlier study has shown that with sufficient water supply, the crop leaves are relatively thin, and the leaf area increases significantly [ 18 ]. On the contrary, under conditions of soil water stress, the leaves are thicker, and the leaf growth rate is slower [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the LAI is an important indicator for measuring the growth characteristics of plant populations. An earlier study has shown that with sufficient water supply, the crop leaves are relatively thin, and the leaf area increases significantly [ 18 ]. On the contrary, under conditions of soil water stress, the leaves are thicker, and the leaf growth rate is slower [ 19 ].…”
Section: Discussionmentioning
confidence: 99%